Perioperative management with glucose solution and insulin - Korušić, Anđelko; Hauptman, Ada; Đuzel, Viktor; Husedžinović, Ino; Horžić, Matija, liječnik; Gašparović, Stojanka; Salamon, Tomislav (2009)
Abstract: The objective of this study was to analyze how preoperative glucose treatment influences the blood glucose level as a measured exponent of surgical stress and to establish the best postoperative replacement considering glucose solutions and insulin. This prospective clinical trial involved 208 non-diabetic patients with normal glucose tolerance, who underwent major surgical procedures and needed 24 hours ICU monitoring postoperatively. Patients were randomly given 5% glucose solution (1000 mL) one day before surgery or after overnight fasting. Group A and group B were randomized to be given 5 different kinds of postoperative replacement with cristalloids and insulin. None of the patients from group A or group B were given glucose solutions during surgical procedures. Blood glucose levels were measured 14 times from the preoperative period until 24 hours after admission to the ICU and the main outcome measure was blood glucose level. All patients had a statistically significant increase in blood glucose levels in comparison to basal levels (p<0.05) in all measurements. All data were processed with descriptive statistics, chi-square test, parametric ANOVA test and ANOVA test with repeated measure, non parametric Kruskal-Wallis test and Mann-Whitney U-test. Statistically significant change was accepted with p<0.05. Preoperative glucose infusion decreased metabolic and endocrine response only during surgery; the smallest increase of postoperative blood glucose level was noticed after administering postoperative non-glucose crystalloid solutions; there is no clinical evidence that one specific postoperative replacement is better than the other; there is no clinical evidence that postoperative use of insulin can decrease or attenuate surgical induced insulin resistance
Bibliografija: 29 jed
Sažetak
Keywords: Glukoza -- Inzulin -- Perioperativna priprema